Investigating and Extending Variation among Friends with Benefits Relationships: Relationship Maintenance and Social Support. Issue 5 (20th October 2019) - Mongeau, Paul A.; van Raalte, Lisa J.; Bednarchik, Lori; Generous, Mark
ABSTRACT: The considerable diversity in friends with benefits relationships (FWBR) is largely unexplored. Therefore, this investigation focuses on differences in the communication of relationship maintenance and social support across FWBR types. Given that communication influences relationship initiation, maintenance, and termination, the frequency of maintenance and support behaviors should differ dramatically across FWBR types. Large differences appeared across five of seven relational maintenance, and all five social support, dimensions, which further validate differences among FWBR types and place communication at the heart of these differences. To overcome limitations of FWBR types, a two-dimensional model of FWBRs (closeness and romantic desire) is introduced to more simply explicate diversity. Finally, we discuss practical and theoretical implications of both the results and the dimensional perspective.